A Rare Type of Balanitis - Bruno Duarte; Ana Rodrigues; Cândida Fernandes (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Syphilis is an old disease and a major public health concern, which is re-emerging in the western world. Atypical syphi- litic presentations can be challenging to diagnose. We present a 23-year-old, HIV-positive man who has sex with men who presented with a 2-week history of an asymptomatic lesion on the glans. Previous topical and systemic treatments proved unsuccessful. Physical examination demonstrated a slightly indurated, ill-defined erythematous plaque over most of the glans. Enlarged, non-tender, bilateral inguinal lymph nodes were palpable. Serological tests revealed a fourfold increase in the VDRL titre (1:8, previously 1:2). A diagnosis of syphilitic balanitis of Follmann was made and complete resolution was achieved with an intramuscular single dose of benzathine penicillin 2.4 MU. Syphilitic balanitis of Follmann represents an uncommon manifestation of primary syphilis, with less than 100 cases reported. Untrea- ted, it will resolve spontaneously, but the patient will remain highly infectious and at-risk for long-term morbidity. In an era in which the number of syphilis cases is increasing sharply both in Western Europe and the United States, all physicians should be aware for the typical and atypical early syphilitic manifestations as they represent opportunities of paramount importance for treatment and epide- mic control.